Analisis Ta'arudh Adillah: Dinamika dan Solusi dalam Ushul Fiqh - Muhammad Sulaiman; Fahmi Royhan; Imam Sucipto (Yayasan Cendekia Gagayunan Indonesia, 2024)
Ta'arudh adillah or conflict between shar'i propositions is one of the fundamental problems in ushul fiqh that requires special attention. The resolution of ta'arudh adillah is crucial to ensure that arguments that appear to be contradictory can be compromised or chosen one of them appropriately, thus maintaining the continuity of understanding Islamic law. This research uses a qualitative approach by analyzing various classical literature by scholars in ushul fiqh. The descriptive-analytical method is applied to explain the concept of ta'arudh adillah, identify the causes of conflict, and evaluate the methods of resolution used by the scholars. The study shows that ta'arudh adillah can be caused by various factors, such as differences in text interpretation, the historical context of the argument, or the level of strength of the argument. The scholars used various methods of resolution, such as tarjih (choosing the stronger argument), nasakh (canceling the previous argument), and jama' (compromising arguments that appear to be contradictory). A deep understanding of the method of resolving ta'arudh adillah can help in applying Islamic law consistently and relevantly. This research makes a significant contribution to the understanding of this concept and its relevance in the modern context.